(3GdOQI GdTQjaI Ydi CUhd GdWQjbIs - (3GdNQhHj, eMeO Hf Ydj, J(B963(3g`s ((3HdbGSe Hf eMeO GdUZjQ Hf eMeOs)
(3ChdgG (B:s
(3GdMeO ddg CMeO Gddg JYGdi aj cd CeQ Pj HGd hYdi cd MGd hCTcQg Ydi eG eQ YdjfG ef ShGHZ GdfYe hceGd GdGNVGds
(3BNQgG (B:s
(3bGd QMeg Gddg JYGdi(B: (3hYhed HGdCNhI aj GdHGbj jQjO ajeG de jhLO ajg ef GdTQhW hGddg GdeSJYGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 292s
(3eYLe GdeDdajf(B: 3 / 509s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs